Increasing the income of SMEs in Maju Jaya women farmers Group (KWT) with e-commerce - Rahmat Robi Waliyansyah; Fafa Nurdyansyah; Joko Siswanto (Universitas Muhammadiyah Magelang, 2023)
This community sercive is carried out to provide understanding and skills to the target audience about internet media (e-commerce) as an effective and efficient means of selling/promoting products; encourage the target audience to use the internet as a means of business development; provide knowledge and skills to the target audience in creating advertising or promotional content on the internet such as on social media; provide assistance to the target audience in utilizing various internet-based market places as a means of selling products. The approach in this program is through the PALS (Participatory Action Learning System) method. The result of this program is the good understanding of partners about marketing through e-commerce; partners are able to create stores on the marketplace and promote through social media independently. The results of internet user assessments state that product marketing through e-commerce has high informative, persuasive (convincing) and intentional (attractive) values.